A Framework of Green Contruction Supply Chain - Lenny Christina Nawangsari; Achmad Hidayat Sutawijaya (International Journal of Supply Chain Management, 2019)
The construction company in a highly competitive environmentare trying to survive by continuing to find ways to create efficiencies and cost-effectiveness, innovation, expertise and timely execution of work. GreenContructionSupply Chain Management has an important role in driving competitive advantage through the performance that takes into environmental factors to provide sustainability in long-term. The purpose of this study was to analyze theFramework ofGreen Construction Supply ChainManagement (GCSCM). The research methodology used the qualitative approach.The data collection will be taken through interviews and observations onkey informants and then analyze the data and draw conclusions byreduction.The study highlights that a the framework model of green construction supply chain inprojectstadium Gelora Bung Karno whicharedefined by three phase. The first phase are called resource or input with consisting of the needs of the client,master plan projectand financing. The second phase area process. The process consisting of tender, designandconstruction. The last phase is theresultor output of the workconsisting withhandover and maintenance.Green Supply Chain Management in the construction company can improving managerial effectiveness in achieving the goals of construction projects for the creation of strategic value and also important factor that could determine thesustainabilityof the company